pH-sensitive Laponite®/doxorubicin/alginate nanohybrids with improved anticancer efficacy - Gonçalves, Mara (2019)
The efficacy of the anticancer drug doxorubicin (Dox) is limited by an insufficient cellular uptake and drug resistance, which is partially due to ion trapping in acidic environments such as the extracellular environment of solid tumors and the interior of endolysosome vesicles. Herein, we describe the preparation and in vitro evaluation of a new type of nanohybrid for anticancer drug delivery which is capable of carrying a high load of the cationic Dox through the cell membrane. In addition, the nanohybrids use the acidic environment of the endolysosomes to release the drug, simultaneously helping to disrupt the endolysosomes and diminishing endolysosome Dox trapping. Furthermore, as the nanohybrid carriers are capable of sustained drug delivery, those that remain in the cytoplasm and still contain Dox are expected to exert a prolonged anticancer activity. Briefly, Dox is loaded onto biocompatible anionic Laponite(®) (LP) nanodisks with a high aspect ratio (25 nm in diameter and 0.92 nm in thickness) through strong electrostatic interactions to get Dox-loaded LP disks. Alginate (AG), a biocompatible natural polymer, is then coated onto the Dox-loaded LP disks (LP/Dox/AG nanohybrids) to prevent the burst release of the drug. The results demonstrate that the nanohybrids have a high encapsulation efficiency (80.8 ± 10.6%), are sensitive to pH and display a sustained drug release behavior. Cell culture experiments indicate that the LP/Dox/AG nanohybrids can be effectively internalized by CAL-72 cells (an osteosarcoma cell line), and exhibit a remarkable higher cytotoxicity to cancer cells than the free Dox. The merits of Laponite(®)/alginate nanohybrids, such as biocompatibility, high loading capacity and stimulus responsive release of cationic chemotherapeutic drugs, render them as excellent platforms for drug delivery.